A novel case of an aggressive superficial spindle cell sarcoma in an adult resembling fibrosarcomatous dermatofibrosarcoma protuberans and harboring an EML4‐NTRK3 fusion. (26th September 2018) - Olson, Nicholas; Rouhi, Omid; Zhang, Linsheng; Angeles, Christina; Bridge, Julia; Lopez‐Terrada, Dolores; Royce, Thomas; Linos, Konstantinos
Abstract : A subset of soft tissue sarcomas often harbors recurrent fusions involving protein kinases. While some of these fusion events have shown utility in arriving at a precise diagnosis, novel fusions in otherwise difficult to classify sarcomas continue to be identified. We present a case of a 40‐year‐old female who noted a lower back nodule in 2010 that was initially labeled as a dermatofibrosarcoma protuberans with fibrosarcomatous transformation. The lesion recurred the following year and metastasized to the groin 6 years later. Because of some morphologic peculiarities, molecular characterization was pursued in the metastatic focus, which revealed the neoplasm was negative for the COL1A1‐PDGFB fusion. However, anchored multiplex polymerase chain reaction for targeted next‐generation sequencing (Archer Dx) detected an EML4‐NTRK3 fusion, which was confirmed by reverse transcription‐PCR, Sanger sequencing and RNA sequencing analysis of the recurrent and metastatic specimens. Although various soft tissue neoplasms involving fusions with NTRK genes are well‐reported, the current case could not be easily classified in any of the established entities. Nevertheless, it raises interesting questions regarding the importance of classification, prognosis, and treatment for some of these tyrosine kinase fusion‐driven sarcomas.